DIFFERENCES IN DETECTION RATES FOR SERIOUS NEONATAL DISEASES BEFORE AND AFTER INSTITUTION OF NEWBORN ROUNDS BY PAEDIATRICIANS IN A PRIVATE SECTOR HOSPITAL - Khan, Afshan; Qazi, Alia; Yousaf, Adnan; Hanif, Ruhila; Agha, Muhammad; Baseer, Muhammad; uddin, Mohiy (Journal of Ayub Medical College Abbottabad, 2010)
Background: Perinatal and infant mortality are two major contributors to child mortality in developing world. It is widely recognised that synergistic efforts by paediatric and obstetric healthcare providers result in improvement of neonatal and infant survival. Close working relationship between the 2 disciplines with attendance of all high risk births by paediatric healthcare providers and routine examination of all neonates is required for this purpose. Objectives were to compare 2 continuums of 100 neonatal cases for detection of serious neonatal disease. One set of neonates being examined by neonatal/paediatric service and other without this service in place. Methods: One hundred Neonatal Exam sheets were selected randomly from records of 2007-2008 and compared with 100 Neonatal Exam Sheets of 2006-2007. Records were analysed for detection of serious neonatal conditions at 24 hours age. Data was analysed using MS EXCEL. Odds ratio was calculated for each disease with Haldane correction. Results: Odds ratio was significantly higher for detection of serious neonatal diseases in 2007-2008 group when neonatal service was actively involved in newborn examinations of all neonates. Highest odds ratios were obtained for detection of Heart Murmur and neonatal sepsis. Conclusions: Newborn Examination within 24-48 hours of birth by trained neonatal healthcare provider is paramount for adequate detection of serious neonatal diseases. Such services should be instituted in all obstetric units for better neonatal outcome. Keywords: Neonatal Exam, High risk neonates, neonatal outcomes